Time-domain behavior of blazar OJ 287 and the binary supermassive black hole conjecture - Ciprini S.; Valtonen M.; Zola S.; Goyal A.; Pihajoki P. (Germany, 2025)
The proper understanding of blazar variability at the various electromagnetic spectral bands is one goal of multifrequency astrophysics. In this frame a peculiar and controversial phenomenology is the periodicity, postulated for long-term radio or optical flux light curves of about a dozen of blazars. The well-known BL Lac object OJ 287 (PKS 0851+202, S3 0851+20, PG 0851+202, z = 0.306) is not only a high-variable, peculiar, extragalactic source with hints for approximatively cyclical optical outbursts, but it also represents a case of substantial intensive and extensive (longterm) multifrequency observations. This rich database allow us a deeper analysis based on a wide range of variability timescales with some recent results that are highlighted here.
7th International Fermi Symposium (IFS2017)